Innovative culture of a teacher of a teaching of higher education: theoretical-methodological and empirical aspects - Serhii Bieliaiev; Ivan Stepanets (Scientific notes of the pedagogical department, 2023)
The article is devoted to the consideration of the problem of formation of innovative culture of a teacher of a pedagogical institution of higher education. the innovative culture of the teacher is considered as a scientific phenomenon, as well as a component of professionalism and a factor in improving the educational process.The purpose of the article is to summarize the results of theoretical research into the essence of innovative culture, the relationship between this phenomenon and the concepts of innovative pedagogical activity, components of professional pedagogical activity and their formation in the process of professional training in the conditions of a pedagogical institution of higher education. The logical relationship between the realization of material and spiritual culture in the innovative activity of an individual is presented. The peculiarity of the formation of an innovative culture in the process of professional pedagogical activity in the conditions of an innovative educational environment is illustrated. The essence of the innovative culture phenomenon is revealed on the basis of axiological and structural-functional approaches and its components are determined. The main factors that determine the formation of the need for the innovative orientation of the teacher’s pedagogical activity in the modern conditions of educational activity in the institution of higher education are revealed. Evaluation criteria were formulated and an empirical study was carried out to determine the levels of formation of innovative culture among teachers of a pedagogical institution of higher education, and the characteristics of individual groups of teachers according to the determined levels were presented. Based on the analysis of the pedagogical characteristics of certain groups of scientific and pedagogical workers, the peculiarities of their atitude to perception, understanding, creation and application of innovations in the educational process were characterized: from active-positive to passive-negative. The key competencies of a modern teacher and their selection criteria are defined, which determine the ability to engage in innovative pedagogical actvity and ensure the effective performance of pedagogical functions and tasks in accordance with the content of the formed innovative culture. According to the results of the conducted research, the conclusions were made that the innovative culture of the teacher is an integrated component of the professionalism of the pedagogical worker at the personal and professional levels. The formation of the teacher’s innovative culture determines the effectiveness and quality of pedagogical activity in the context of the development of the innovative educational environment of the institution of higher education.